Public space in Quito Ecuador. An innovative tool to employ the territorial development - Gierhake, Klaus (2016)
Fil: Gierhake, Klaus. Universidad Justus Liebig. Centro para el Desarrollo Internacional y Investigación Ambiental; Alemania.